Overlapping cell population expression profiling and regulatory inference in C. elegans. (December 2016) - Burdick, Joshua; Walton, Travis; Preston, Elicia; Zacharias, Amanda; Raj, Arjun; Murray, John
Abstract Background Understanding gene expression across the diverse metazoan cell types during development is critical to understanding their function and regulation. However, most cell types have not been assayed for expression genome-wide. Results We applied a novel approach we term "Profiling of Overlapping Populations of cells (POP-Seq)" to assay differential expression across all embryonic cells in the nematodeCaenorhabditis elegans . In this approach, we use RNA-seq to define the transcriptome of diverse partially overlapping FACS-sorted cell populations. This identified thousands of transcripts differentially expressed across embryonic cells. Hierarchical clustering analysis identified over 100 sets of coexpressed genes corresponding to distinct patterns of cell type specific expression. We identified thousands of candidate regulators of these clusters based on enrichment of transcription factor motifs and experimentally determined binding sites. Conclusions Our analysis provides new insight into embryonic gene regulation, and provides a resource for improving our knowledge of tissue-specific expression and its regulation throughoutC. elegans development.